Numerical flow noise simulation of an axial fan with a Lattice-Boltzmann solver - Antoniou, Evangelos; Romani, Gianluca; Jantzen, Andreas; Czwielong, Felix; Schoder, Stefan (Acta Acustica, 2023)
In this paper, a transient and compressible solver based on the Lattice-Boltzmann Method/Very Large Eddy Simulation (LBM/VLES) approach is employed to predict unsteady flow physics and flow-induced noise generation of a low-pressure axial fan. Aerodynamic and aeroacoustic measurements provided by the European Acoustics Association (EAA) benchmark platform are used for validation purposes. Boundary and design operating conditions are applied to the numerical model to replicate the experimental setup. Simulation and experimental data are compared, showing an excellent agreement in terms of fan efficiency with less than 1% deviation, as well as broadband and tonal noise within 0.7 dBA in terms of overall sound pressure level. An advanced post-processing analysis is performed to shed light on the noise generation mechanism in tip clearance. It is observed that both fine random turbulent structures and large coherent vortices are generated in the tip gap. The continuous impingement of the fine turbulence with the following blades and the blade itself is responsible for the radiation of broadband noise, while the interaction between the large coherent tip vortices, spinning at a lower angular velocity with respect to the fan shaft, and the following blades leads to the generation of narraowband peaks at sub-harmonics of the blade-passing frequencies. Finally, a beamforming analysis further confirms that the main noise sources are located in the blade tip clearance and tip regions.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Aeroacoustics; Axial fans; Computational Fluid Dynamics; Lattice-Boltzmann Method; Sub-harmonic noise